Estimación de carbono en tres depósitos naturales del ecosistema herbazal de páramo en la microcuenca Cachipata, comunidad Llucud, cantón Chambo - Ruiz Carrera, Cristian Andres (2018)
The goal of the present research was to estimate the organic coal (CO) content carbon in in aerial biomass (BA), subterranean (BS), necromass (N) and a floristic inventory in the moor grassland ecosystem (EHP) of the hydrological territory of the la Microcuenca Cachipata (THMC). A random sampling was carried out; thought ArcGIS software; considering 69 sampling points in five altitudinal types (C1 ~ C5), with a confidence level of 95%.For the sample collection BA y N Random plots were used at ground level and for BS the drilling method collecting 207 samples at three depths (0-10, 10-20, 20-30) cm. Considering altitude and CO, the BA y N in C5 reports the highest (CO) with average value of (1.64 - 0.88) kg m-2 respectively as for BS the CO at three depths, he determined a variation inversely proportional to the depth while in relation to the altitude it doesn’t notice significant differences between them. The floristic diversity registered 164 individuals grouped in 11 species and 8 families, determining a greater number of families and species in C1 species in C1 located between (3601 - 3700) m.s.n.m. The species with greater importance value are: Calamagrostis intermediate (55%), Festuca procera y Pernettya prostrata The Shannon index showed a value of 0.72 and the Simpson index showed a value of 0.86. This research allows us to know the importance of biomass in kidnapping of coal in order to diagnostic the environmental goods and services offered by the THMC.